Effect of Cross-Linkers on Activity of Alcohol Dehydrogenase Immobilized on Polyaniline Magnetic Nanoparticles - Jin, Lihua; Li, Ye; Ren, Xiang Hao (Asian Journal of Chemistry, 2015)
In this study, alcohol dehdyrogenase (ADH) was immobilized on polyaniline magnetic nanoparticles (PAMP), which were used to completely recover the immobilized enzyme. When glutaraldehyde was used as a cross linker to immobilize alcohol dehdyrogenase on polyaniline magnetic nanoparticles, no alcohol dehdyrogenase activity was observed after immobilization. However, when 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) was used as a cross linker, immobilized alcohol dehdyrogenase was found to display improved activity. The Kcat values of the free and immobilized alcohol dehdyrogenases were determined to be 82 and 17 mM/min/mg protein, respectively. Immobilized alcohol dehdyrogenase showed enhanced stability under acidic conditions at pH 4.5. While the activity of free alcohol dehdyrogenase was zero, the activity of immobilized alcohol dehdyrogenase was 50 % of its original activity at pH 4.5. The immobilized enzyme was also highly stable under rigorous shaking conditions relative to free alcohol dehdyrogenase. After 30 days of incubation at room temperature and 200 rpm, the residual activity of the free enzyme was zero, whereas that of the immobilized alcohol dehdyrogenase was 90.7 % after 60 days. The immobilized alcohol dehdyrogenase was recovered after completion of the enzyme reaction and it was still active after 15 consecutive reactions. The activity of immobilized alcohol dehdyrogenase was over 90 % of its original activity.